Self-Care Behavior, Psychological Distress, and Quality of Life Among Patients with Diabetes: A Cross-Sectional Study in Vietnam - Dang Thi Nguyen Chi; Tran Mai Trinh (CV. Tripe Konsultan, 2026)
This study identified self-care, diabetes-related psychological distress, QoL, and to examine associations between three contents among patients with diabetes at Tam Tri General Hospital, Dong Thap province. A cross-sectional study was conducted from Sept 2024 to May 2025 among 200 patients with type 2 diabetes. Self-care, psychological distress, and QoL were assessed using validated Vietnamese versions of SDSCA, DDS-17, and WHOQOL-BREF. Chi-square tests examined associations between self-care level, psychological distress, and QoL. Most participants were ≥45 years (88%), female (64.5%), urban residents (95.5%), and married (78.5%). Good self-care was reported by 97.5% of patients; adherence was 100% for treatment and foot care, 74% for diet, 54% for physical activity, and 7% for glucose monitoring. Psychological distress levels were low (43%), moderate (41%), and high (16%), with regimen-related (69%) and emotional (65%) distress most common. QoL was low in 20%, moderate in 55%, and high in 25% of participants. Good self-care was significantly associated with lower distress (p = 0.007) and higher QoL (p = 0.001). Medication and foot-care adherence were high, but gaps remain in diet, activity, and glucose monitoring. Strengthening comprehensive self-management and integrating psychosocial support could improve outcomes and QoL for patients with diabetes.